The implications of abnormal stereopsis in typical and atypical development - Smith, Danielle (2017)
A remarkable feature of the human visual system is that it is possible to extrapolate a large amount of information about the three-dimensional structure of the environment simply from the pattern of light that falls on the retinae. This information is derived from a number of different cues to depth. The mechanisms by which these are encoded in the brain, combined into an overall percept, and subsequently interpreted are reasonably well understood. However, individuals who participate in studies of depth perception tend to have acute sensitivity to certain depth cues, meaning that the consequences of individual differences in depth perception have been largely ignored. In this thesis I investigate how individual differences in the ability to utilise a single cue, binocular disparity, affects overall perception of depth and then go on to explore the wider function significance of such a deficit. I also examine whether an underlying deficit in stereopsis may account for some of the perceptual differences observed in autism spectrum disorder (ASD).